Jurisdiction of the International Criminal Court over the crimes committed on the territory of Afghanistan - Radmanović, Jelena S (Glasnik Advokatske komore Vojvodine, 2021)
The subject of this paper are, in the first place, the territorial and personal aspects of the jurisdiction of the International Criminal Court in relation to crimes committed in the territory or in connection with the armed conflict in the territory of Afghanistan. During 2020, the International Criminal Court determined the fulfillment of the conditions for initiating an investigation into crimes committed in Afghanistan, or in connection with the armed conflict in Afghanistan. The paper is based on linguistic, normative and systematic analysis of current regulations in the field of international public and international criminal law, and linking the relevant provisions with the circumstances under which crimes were committed in Afghanistan and finally drawing conclusions on the fulfillment of necessary conditions for the Court to conduct criminal proceedings. The result of the analysis leads to the conclusion that the conditions for opening an investigation into crimes committed in Afghanistan or in connection with the armed conflict on the territory of Afghanistan are met, and the launch of the investigation is particularly important in the context of withdrawal of US troops and takeover of Afghanistan by the Taliban, given that the Office of the Prosecutor is authorized to undertake the necessary investigative actions, which ultimately facilitates the process of gathering evidence during the period in which the criminal offenses continue to be committed.